Factors Influencing Blood Donation Interest in Makassar City Society - Sitti Rahbiah Akram; Rahmita Rahmita; Muhammad Yunus; Achmad Mulyaone Putra Rusdi (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
The demand for blood continues to increase each year. The lack of interest in blood donation among the public leads to insufficient blood supply at blood banks, especially in Makassar city. This study was conducted to identify the factors that influence the public's interest in blood donation in Makassar. This is a quantitative research with a cross-sectional design and an analytical observational approach, using a sample of 100 people who reside in Makassar. The sampling technique used was accidental sampling, and primary data was collected using a questionnaire that had been tested for validity and reliability. Data analysis was conducted using univariate and bivariate analysis with the chi-square test. Overall, the results of the study showed that the public's interest in blood donation in Makassar was very good, with 75% (75 people) of the total 100 respondents expressing interest. The frequency based on gender and age was dominated by females at 76%, and the age range of 20-29 years accounted for 40%. The frequency of employment status showed that 45% were employed, while 55% were unemployed. Respondents' knowledge level was found to be good, with 95% demonstrating good knowledge. Based on the chi-square test, it was found that there was no significant relationship between knowledge (p= 1.000>p=0.05), gender (p= 1.000>p=0.05), and occupation (p= 0.357>p=0.05) and the interest in blood donation. However, age (p= 0.010<p=0.05) was found to have an effect on the public's interest in blood donation in Makassar. Interviews also revealed that there are other factors affecting blood donation interest, such as attitude, medical history, body weight, and other external factors. Keyword: Interest in Donation, Blood Donation, Makassar Community